IMPLEMENTATION OF DISCOVERY LEARNING USING INTERACTIVE FLIPBOOK MEDIA IN CHEMISTRY TO IMPROVE MOTIVATION AND LEARNING OUTCOMES IN SENIOR HIGH SCHOOL - Ummah, Dinda Khoirul; Prasasti, Tirangga Lutfi; Amalia, Nurul; Subaidi, Faizatunnisa; Auliya, Rima; Novita, Dian; Hadibyono, Luluk; Rizqullah, Aflah Farchan (UNESA Journal of Chemical Education, 2025)
This study is a Classroom Action Research (CAR) aimed to measuring the improvement in students’ motivation and learning outcomes through the implementation of the Discovery Learning model using interactive flipbook media on acid-base material. The sample used consisted of 30 students from class XI-3 at SMA Negeri 14 Surabaya. The research consisted of four stages: planning, implementation, observation, and reflection. The instruments used were pre-test and post-test to assess the improvement in cognitive learning outcomes, and a learning motivation questionnaire to measure students’ affective aspects. The results showed that the average N-Gain score increased from 0.61 (moderate category) in the first cycle to 0.76 (high category) in the second cycle. A significant improvement was also observed in students’ learning motivation, increasing from an average percentage of 52.26% in the first cycle to 84.03% in the second cycle after the learning process was carried out. Based on these data, it can be concluded that the application of the discovery learning model using interactive flipbook media is effective in enhancing students’ motivation and learning outcomes in chemistry learning, particularly in acid-base material. The results also indicate that this model and media can serve as an innovative and engaging alternative strategy for future chemistry education.